ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS E-LEARNING AMONG UNDERGRADUATE MEDICAL STUDENTS IN GAUHATI MEDICAL COLLEGE, GUWAHATI, ASSAM – A PILOT STUDY - MITRA BHATTACHARYYA; PRAN PRATIM SAIKIA; S RENUKA SINGH; DWIPEN KHANIKAR; LAKHIMI BORAH; DIPTIMAYEE DEVI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective is to conduct a pilot study to assess the knowledge, attitude, and practice (KAP) of e-learning among undergraduate medical students. Methods: An observational, questionnaire-based, and cross-sectional pilot study was carried out for 1 month among undergraduate medical students of Gauhati Medical College and Hospital (13 from each phase of MBBS). We compared the responses of KAP among the participants of each phase of MBBS. Results: A total of 52 undergraduate medical students participated in the study. 43 (82.69%) were male and 9 (17.31%) were female with a mean age of 21.63±1.63. 18 (34.62%) owned a personal laptop or computer and 45 (86.54%) of them had access to Internet facility. Majority of them i.e. 48 (92.31%) used only smartphones and were competent in using software applications. Most of them agreed that e-learning should be supplemented in regular teaching curriculum (76.92%). Statistical analysis was done by using one-way analysis of variance and post hoc test (Tukey), to know the mean KAP score of e-learning among the participants of three phases of MBBS and also the significance of KAP towards e-learning. It showed that p value was significant in case of knowledge and practice but not in case of attitude. Conclusion: The results that were found in each category of KAP toward e-learning were almost comparable to other studies which were conducted using a structured and validated questionnaire. Thus e-learning can be a useful tool in enhancing the learning experience among students.